The Impact Of Diversity and Inclusion Policies In Human Resource Management On Organizational Performance - Hermyn Benny Hina (International Journal of Management and Business Economics, 2024)
Diversity and inclusion policies in human resource (HR) management have become an important topic in the context of modern organizational management. This research aims to investigate the impact of diversity and inclusion policies in HR management on organizational performance. The research method used is a qualitative approach by conducting a literature review to collect information about the concepts of diversity, inclusion, HR management and organizational performance. The results of the analysis show that diversity and inclusion policies in HR management have a positive impact on organizational performance. This happens because the policy encourages the creation of an inclusive work environment, where every individual feels valued and recognized, thereby increasing employee motivation, creativity and productivity. Apart from that, this policy can also improve the company's reputation and attractiveness in the eyes of prospective employees, as well as increase employee satisfaction and loyalty. This research contributes to the understanding of the importance of diversity and inclusion policies in HR management as a strategy to improve organizational performance. Provide recommendations for future research, such as areas that need further research or methodological approaches that can be used to gain a deeper understanding of this topic. By making contributions as mentioned above, your research can provide a better understanding of the importance of diversity and inclusion policies in HR management to improve organizational performance